The Construction of Religious Freedom in Indonesian Legislation: A Perspective of Maqāṣid Ḥifẓ Al-Dīn - Lathifah, Anthin; Hapsin, Abu -; Rofiq, Ahmad; Hidayatullah, M. Arief (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2022)
The Indonesian state has legal provisions of religious freedom contained in the constitution and its derivatives legislation. This article aims to discuss religious freedom in Indonesian legislation from the perspective of maqāṣid hifẓ al-dīn. This study is the result of qualitative research using a content analysis approach. From the results of the discussion, it is known that the freedom of religion in Indonesian legislation includes freedoms to choose belief (Belief in One Supreme God), to worship, and to express religion. These provisions are in line with hurriyyah al-'i'tiqād Ibn 'Āsyūr and al-ḥurriyyah fī al-dīn al-Zuhailī regarding freedom of worship but are not in accordance with al-Zuhaili's opinion about freedom of belief, an area of personal choice when one may choose to be religious or not. The contradiction occurs because all Indonesian citizens must believe in One and Only God as the first precept of Pancasila and make six religions as religions recognized by the State as contained in Presidential Decree No. 1/1965 (PNPS Act). Therefore, it is necessary to reconstruct the law and values of religious freedom contained in the PNPS Act, especially in its implementation.